The Association between Auditor Choice, Ownership Retained, and Earnings Disclosure by Firms Making Initial Public Offerings - COPLEY, PAUL A.; DOUTHETT Jr, EDWARD B. (Contemporary Accounting Research, 2002)
Using a system of three simultaneous equations, we test the predictions of Datar, Feltham, and Hughes 1991 and Hughes 1986 between auditor choice, earnings disclosures, and retained ownership in U.S. firms making initial public offerings of securities. Using a sample of initial public offerings between 1990 and 1997, we find that the demand for high-quality auditors increases with firm risk. Additionally, we find that auditor choice, earnings disclosure, and risk are determinants of retained ownership, which is consistent with the predictions of Datar et al. and Hughes that auditor choice and direct disclosure are substitute signals for ownership retention. Further, our results suggest that the signals chosen (i.e., retained ownership, auditor choice, and disclosure) are related through their cost structures and are chosen jointly to minimize the overall cost to the entrepreneur.